Controlled experiments in lithic technology and function - Marreiros, Joao (2021)
From the earliest manifestations of tool production, technologies have played a fundamental role in the acquisition of different resources and are representative of daily activities in the lives of ancient humans, such as hunting (stone-tipped spears) and meat processing (chipped stone tools) (Lombard 2005; McPherron et al. 2010; Lombard and Phillipson 2010; Brown et al. 2012; Wilkins et al. 2012; Sahle et al. 2013; Joordens et al. 2015; Ambrose 2001; Stout 2001). Yet many questions remain, such as how and why technological changes took place in earlier populations, and how technological traditions, innovations, and novelties enabled hominins to survive and disperse across the globe (Klein 2000; McBrearty and Brooks 2000; Henshilwood et al. 2001; Marean et al. 2007; Brown et al. 2012; Režek et al. 2018). By understanding how and why past humans used different tools, we could answer key questions related to human technological evolution, such as ecological decision-making processes, as well as cultural transmission dynamics (Eerkens and Lipo 2007; Whiten et al. 2009; Goodale and Andrefsky 2015; Lycett et al. 2015; Ferguson and Neeley 2010; Morgan et al. 2015).